Analisis Kritik Sastra Baru terhadap Penokohan Edmund Pevensie yang Menggambarkan Persoalan Self-Centeredness dalam Novel Berjudul The Lion, the Witch, and the Wardrobe - Hidayat, Nur Intan Manylanti (Linguistika Kultura, 2024)
Among various children's literary works, the famous novel "Narnia" by C. S. Lewis has an interesting storyline caused by good characterization. One of the characters; Edmund Pevensie suggests the issue of self-centeredness in the first book of the series titled "The Lion, the Witch, and the Wardrobe". His desire for position and authority have led him to be self-centered. This paper aims to analyze Edmund's self-centered characteristics and character types. It utilized a descriptive qualitative method and the New Criticism approach to examine the element of character in the book. The researcher found that three characteristics of Edmund are portrayed as self-centeredness: jealousy, hatred, and arrogance. Moreover, it is also believed that Edmund is considered a round and dynamic type of character which marked by his transformation at the end of the story. It includes the characteristics of regretful, obedient, and helpful.